2018
DOI: 10.17098/amj.436537
|View full text |Cite
|
Sign up to set email alerts
|

Violence Against Healthcare Workers in the Light of White Code Data

Abstract: Objectives:We aimed to analyse the data on violence against healthcare workers in an hospital according to the White Code (WC) reports implemented, to prevent such violence events and discuss some solutions about it. Materials and Methods: In the study, WC data of Hamidiye Etfal Training and Research Hospital for years 2016 and 2017 were obtained and examined with appropriate statistical methods. Results: 209 violence events were declared. 191 of the healthcare workers were victims of violence in these two yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
2
2
Order By: Relevance
“…31 In this study, men were found to be exposed to physical violence and verbal harassment more than a woman, which is consistent with some previous study results. 5,24,32,33 Unlike our results, WPV in an emergency was found to be similarly experienced by male and female physicians (79% vs 75%; P = .65, respectively). 32 The study found that doctors were more vulnerable to WPV, which is consistent with some previous research, 5,10,33 while some research did not support this result, 34,35 which may be because physicians are the front line of health care in the Turkish health care system.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…31 In this study, men were found to be exposed to physical violence and verbal harassment more than a woman, which is consistent with some previous study results. 5,24,32,33 Unlike our results, WPV in an emergency was found to be similarly experienced by male and female physicians (79% vs 75%; P = .65, respectively). 32 The study found that doctors were more vulnerable to WPV, which is consistent with some previous research, 5,10,33 while some research did not support this result, 34,35 which may be because physicians are the front line of health care in the Turkish health care system.…”
Section: Discussioncontrasting
confidence: 96%
“…5,24,32,33 Unlike our results, WPV in an emergency was found to be similarly experienced by male and female physicians (79% vs 75%; P = .65, respectively). 32 The study found that doctors were more vulnerable to WPV, which is consistent with some previous research, 5,10,33 while some research did not support this result, 34,35 which may be because physicians are the front line of health care in the Turkish health care system. These variations may be partially explained by societal or cultural variations that have an impact on personal risk factors in particular nations.…”
Section: Discussioncontrasting
confidence: 96%
“…A practice was initiated by the Ministry of Health to report violent incidents and provide legal aid to healthcare workers who were subjected to violence, and a "113 White Code Call Center" was established to provide 24/7 service [6]. The calls to the center are mostly being made by physicians [4,7]. Unfortunately, intern physicians are among the groups subjected to violence, which affects both their education processes and their future professional practices negatively [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…(8,9,10). Violence against HCWs is mostly encountered in emergency services (11,12,13).…”
mentioning
confidence: 99%